UV photocuring adhesive and preparation method thereof

Through the preparation of modified zinc oxide and its application in UV photocuring glue, the problem of refractive index mismatch in optical device connections is solved, and UV photocuring glue with high refractive index, excellent mechanical strength and antibacterial properties is achieved, which is suitable for optical films and other fields.

CN119709026APending Publication Date: 2025-03-28AN HUI SUNTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411917191.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the existing UV light curing glue is connected to the optical device, the refractive index does not match the optical device, resulting in light source interference and noise, and lacks aging resistance.

Method used

Modified zinc oxide was prepared by surface coating and grafting reaction of zinc epoxidized and polyhexamethylene guanidine hydrochloride with silane coupling agent KH-560 and mixed with hard monomer, soft monomer, active diluent, photoinitiator and defoaming agent to prepare UV photocuring glue with high refractive index and excellent mechanical strength.

Benefits of technology

It improves the refractive index, chemical stability, scratch resistance and mechanical strength of UV light curing glue, and at the same time enhances its antibacterial properties and aging resistance, and is suitable for optical films and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207089160000091
    Figure BDA0005207089160000091
  • Figure BDA0005207089160000101
    Figure BDA0005207089160000101
Patent Text Reader

Abstract

The invention belongs to the technical field of curing adhesives, and provides a UV photocuring adhesive and a preparation method thereof, the UV photocuring adhesive comprises the following raw materials by weight: 20-35 parts of a hard monomer, 30-55 parts of a soft monomer, 6-10 parts of modified zinc oxide, 20-35 parts of an active diluent, 1-5 parts of a photoinitiator, and 0.1-1 part of an antifoaming agent; the preparation method of the modified zinc oxide comprises the following steps: adding epoxidized zinc oxide and polyhexamethylene guanidine hydrochloride into deionized water, performing ultrasonic dispersion, stirring, filtering, washing and drying to obtain the modified zinc oxide. The UV photocuring adhesive provided by the invention has high refractive index, excellent mechanical strength and antibacterial property, and has excellent application prospects in the fields of optical lenses, imaging devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of curing adhesives, and in particular relates to a UV light curing adhesive and a preparation method thereof. Background Art

[0002] Prism film, also known as brightness enhancement film (BEF), is a new type of high-performance optical film. Its outer surface has a microscopic prism array structure, which enables it to significantly improve the luminous efficiency of the backlight system. Prism film is usually made of optical-grade transparent plastics such as PET as a substrate, and a prism structure is micro-replicated on its surface by UV light-curing adhesive. In the production of prism film, UV light-curing adhesive plays a vital role. It can not only firmly fix the prism structure on substrates such as PET, but also ensure the light transmittance and brightening effect of the prism film. At the same time, UV light-curing adhesive also has excellent resistance to boiling and high-temperature baking, which can ensure that the performance of the prism film will not deteriorate due to environmental changes during use.

[0003] Common UV curing adhesives are usually composed of prepolymers, monomers and photoinitiators. Prepolymers are the skeleton of UV curing adhesives and provide key properties of the adhesive layer, such as tensile strength, shear strength, hardness, etc. Monomers are also called active diluents. Their main function is to adjust the viscosity and participate in the polymerization reaction. They have an important influence on the properties of the adhesive layer, such as hardness, toughness and curing process. Photoinitiators play a decisive role in the curing rate of UV curing adhesives and have a certain influence on the properties of the adhesive layer.

[0004] At present, with the continuous development of the industry, it has higher requirements for the optical properties of light-curing adhesives. When UV light-curing adhesives are used to connect optical devices, they require higher hardness, light transmittance and other optical properties. The refractive index is an important optical performance indicator of UV light-curing adhesives. When the refractive index of UV light-curing adhesives and the refractive index of optical devices do not match each other near the light source, it will cause interference and noise from the light source. Therefore, in order to optimize this connection, it is very necessary to reduce the mismatch of the refractive index and improve the refractive index of UV light-curing adhesives to achieve effective control. At the same time, UV light-curing adhesives are also required to have advantages such as aging resistance. Summary of the invention

[0005] The object of the present invention is to provide a UV light-curing adhesive and a preparation method thereof, so as to solve one of the technical problems mentioned in the background technology.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The first aspect of the present invention provides a UV light curing adhesive, which comprises the following raw materials in parts by weight:

[0008] 20-35 parts of hard monomer, 30-55 parts of soft monomer, 6-10 parts of modified zinc oxide, 20-35 parts of active diluent, 1-5 parts of photoinitiator, 0.1-1 parts of defoamer;

[0009] The preparation steps of the modified zinc oxide are as follows:

[0010] Add epoxidized zinc oxide and polyhexamethylene guanidine hydrochloride into deionized water, disperse them by ultrasonic for 15-20 minutes, stir them at room temperature for 46-48 hours, filter, wash and dry them to obtain modified zinc oxide.

[0011] As a further embodiment of the present invention, the usage ratio of epoxidized zinc oxide, polyhexamethylene guanidine hydrochloride and deionized water is 0.2-0.3 g: 0.5-0.6 g: 100 mL.

[0012] As a further embodiment of the present invention, the preparation steps of epoxidized zinc oxide are as follows:

[0013] Add silane coupling agent KH-560 to ethanol aqueous solution, adjust the pH to 8-8.5, heat to 30-35°C, stir and hydrolyze for 1.5-2h, add nano zinc oxide, ultrasonically disperse until uniform, heat to 70-75°C, reflux for 3-3.5h, stop heating, separate, wash, and vacuum dry to obtain epoxidized zinc oxide.

[0014] As a further solution of the present invention, the usage ratio of silane coupling agent KH-560, ethanol aqueous solution and nano zinc oxide is 5-6g:100g:5-6.5g.

[0015] As a further embodiment of the present invention, the hard monomer is at least one of o-phenylphenoxyethyl acrylate, N,N-dimethylacrylamide, acryloylmorpholine, 2-phenoxyethyl acrylate and benzyl acrylate.

[0016] As a further embodiment of the present invention, the soft monomer is at least one of butyl acrylate, isooctyl acrylate, sec-butyl acrylate, stearic acid methacrylate and isodecyl methacrylate.

[0017] As a further solution of the present invention, the active diluent is at least one of ethoxylated bisphenol A dimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate and di(trimethylolpropane)tetraacrylate. Adding the active diluent in the reaction can participate in the polymerization reaction and improve the curing performance of the system. In addition, it can also reduce the emission of organic volatilization in the over-cured system, so that the light-curing system meets the characteristics of environmental friendliness.

[0018] As a further embodiment of the present invention, the photoinitiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0019] As a further embodiment of the present invention, the defoaming agent is at least one of phenylethyl oleate, lauryl phenylacetate and polydimethylsiloxane.

[0020] A second aspect of the present invention provides a method for preparing a UV light-curing adhesive, comprising the following steps:

[0021] Weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70-90°C and stir to react for 0.5-1.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75-80°C, continue stirring to react for 1-1.5h, and obtain UV light-curing adhesive after cooling.

[0022] Beneficial effects of the present invention:

[0023] The UV light-curing adhesive provided by the present invention is prepared by mixing hard monomers, soft monomers, modified zinc oxide, active diluents, photoinitiators and defoamers. By controlling the types and amounts of monomers and adding modified zinc oxide, active diluents, photoinitiators and defoamers, the UV light-curing adhesive has a high refractive index, excellent mechanical strength and antibacterial properties, and has excellent application prospects in the fields of optical films and the like.

[0024] In the present invention, high-refractive-index zinc oxide is uniformly dispersed in a polymer to improve the refractive index, chemical stability, scratch resistance and mechanical strength of UV light-curing adhesive. However, the surface of nano zinc oxide has a high polarity and a high surface energy, so it is very easy to agglomerate in the polymer and has poor compatibility with the polymer. Therefore, in the present invention, silane coupling agent KH-560 is first used to surface-coat nano zinc oxide, thereby reducing the surface energy of zinc oxide, reducing the agglomeration phenomenon, improving the dispersibility and compatibility in the polymer, and then grafting reaction with polyhexamethylene guanidine hydrochloride occurs to further improve the dispersibility of nano zinc oxide and the compatibility of the polymer. At the same time, the epoxy group on the surface of zinc oxide reacts with the active amino group on the polyhexamethylene guanidine hydrochloride, so that the surface of zinc oxide particles carries guanidine groups, and the guanidine groups form ion pairing with phospholipids in the cell membranes of bacteria, viruses, microorganisms, etc., so that the bacterial membrane collapses, thereby further improving the antibacterial effect, thereby greatly improving the antibacterial performance and aging resistance of UV light-curing adhesive.

[0025] The method for preparing a UV light-curing adhesive provided by the present invention has a simple operation process, low cost and is suitable for large-scale production. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment provides a UV light curing adhesive, which includes the following raw materials in parts by weight:

[0029] 20 parts of o-phenylphenoxyethyl acrylate, 30 parts of isooctyl acrylate, 6 parts of modified zinc oxide, 20 parts of pentaerythritol triacrylate, 1 part of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 0.1 parts of phenethyl oleate.

[0030] The preparation steps of the UV light curing adhesive are as follows:

[0031] Step 1, add 5g of silane coupling agent KH-560 to 100g of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), adjust the pH to 8, heat to 30°C, stir and hydrolyze for 1.5h, add 5g of nano zinc oxide, ultrasonically disperse until uniform, heat to 70°C, reflux for 3h, stop heating, separate, wash, and place in a 50°C vacuum drying oven to dry for 12h to obtain epoxidized zinc oxide;

[0032] Step 2, adding 0.2 g of epoxidized zinc oxide and 0.5 g of polyhexamethylene guanidine hydrochloride into 100 mL of deionized water, ultrasonically dispersing for 15 min, stirring at room temperature for 46 h, filtering, washing, and drying to obtain modified zinc oxide;

[0033] Step 3, weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 0.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75°C, continue stirring to react for 1h, and obtain UV light-curing adhesive after cooling.

[0034] Example 2

[0035] This embodiment provides a UV light curing adhesive, which includes the following raw materials in parts by weight:

[0036] 20 parts of o-phenylphenoxyethyl acrylate, 30 parts of isooctyl acrylate, 6 parts of modified zinc oxide, 20 parts of pentaerythritol triacrylate, 1 part of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 0.1 parts of phenethyl oleate.

[0037] The preparation steps of the UV light curing adhesive are as follows:

[0038] Step 1, add 6g of silane coupling agent KH-560 to 100g of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), adjust the pH to 8, heat to 30°C, stir and hydrolyze for 1.5h, add 5g of nano zinc oxide, ultrasonically disperse until uniform, heat to 70°C, reflux for 3h, stop heating, separate, wash, and place in a 50°C vacuum drying oven to dry for 12h to obtain epoxidized zinc oxide;

[0039] Step 2, adding 0.3 g of epoxidized zinc oxide and 0.6 g of polyhexamethylene guanidine hydrochloride into 100 mL of deionized water, ultrasonically dispersing for 15 min, stirring at room temperature for 46 h, filtering, washing, and drying to obtain modified zinc oxide;

[0040] Step 3, weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 0.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75°C, continue stirring to react for 1h, and obtain UV light-curing adhesive after cooling.

[0041] Example 3

[0042] This embodiment provides a UV light curing adhesive, which includes the following raw materials in parts by weight:

[0043] 35 parts of o-phenylphenoxyethyl acrylate, 55 parts of isooctyl acrylate, 10 parts of modified zinc oxide, 35 parts of pentaerythritol triacrylate, 5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 1 part of phenethyl oleate.

[0044] The preparation steps of the UV light curing adhesive are as follows:

[0045] Step 1, add 5g of silane coupling agent KH-560 to 100g of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), adjust the pH to 8, heat to 30°C, stir and hydrolyze for 1.5h, add 5g of nano zinc oxide, ultrasonically disperse until uniform, heat to 70°C, reflux for 3h, stop heating, separate, wash, and place in a 50°C vacuum drying oven to dry for 12h to obtain epoxidized zinc oxide;

[0046] Step 2, adding 0.2 g of epoxidized zinc oxide and 0.5 g of polyhexamethylene guanidine hydrochloride into 100 mL of deionized water, ultrasonically dispersing for 15 min, stirring at room temperature for 46 h, filtering, washing, and drying to obtain modified zinc oxide;

[0047] Step 3, weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 0.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75°C, continue stirring to react for 1h, and obtain UV light-curing adhesive after cooling.

[0048] Example 4

[0049] This embodiment provides a UV light curing adhesive, which includes the following raw materials in parts by weight:

[0050] 28 parts of o-phenylphenoxyethyl acrylate, 45 parts of isooctyl acrylate, 8 parts of modified zinc oxide, 25 parts of pentaerythritol triacrylate, 2 parts of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 0.5 parts of phenethyl oleate.

[0051] The preparation steps of the UV light curing adhesive are as follows:

[0052] Step 1, add 5g of silane coupling agent KH-560 to 100g of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), adjust the pH to 8, heat to 30°C, stir and hydrolyze for 1.5h, add 5g of nano zinc oxide, ultrasonically disperse until uniform, heat to 70°C, reflux for 3h, stop heating, separate, wash, and place in a 50°C vacuum drying oven to dry for 12h to obtain epoxidized zinc oxide;

[0053] Step 2, adding 0.2 g of epoxidized zinc oxide and 0.5 g of polyhexamethylene guanidine hydrochloride into 100 mL of deionized water, ultrasonically dispersing for 15 min, stirring at room temperature for 46 h, filtering, washing, and drying to obtain modified zinc oxide;

[0054] Step 3, weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 0.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75°C, continue stirring to react for 1h, and obtain UV light-curing adhesive after cooling.

[0055] Example 5

[0056] This embodiment provides a UV light curing adhesive, which includes the following raw materials in parts by weight:

[0057] 26 parts of o-phenylphenoxyethyl acrylate, 50 parts of isooctyl acrylate, 8 parts of modified zinc oxide, 30 parts of pentaerythritol triacrylate, 2 parts of 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, and 0.2 parts of phenethyl oleate.

[0058] The preparation steps of the UV light curing adhesive are as follows:

[0059] Step 1, add 5.5g of silane coupling agent KH-560 to 100g of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), adjust the pH to 8, heat to 30°C, stir and hydrolyze for 1.5h, add 5.5g of nano zinc oxide, ultrasonically disperse until uniform, heat to 70°C, reflux for 3.5h, stop heating, separate, wash, and place in a 50°C vacuum drying oven to dry for 12h to obtain epoxidized zinc oxide;

[0060] Step 2, adding 0.25 g of epoxidized zinc oxide and 0.55 g of polyhexamethylene guanidine hydrochloride into 100 mL of deionized water, ultrasonically dispersing for 20 min, stirring at room temperature for 48 h, filtering, washing, and drying to obtain modified zinc oxide;

[0061] Step 3, weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 01.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 80°C, continue stirring to react for 1.5h, and obtain UV light-curing adhesive after cooling.

[0062] Comparative Example 1

[0063] This embodiment provides a UV light-curing adhesive without adding modified zinc oxide, and includes the following raw materials by weight:

[0064] 20 parts of o-phenylphenoxyethyl acrylate, 30 parts of isooctyl acrylate, 20 parts of pentaerythritol triacrylate, 1 part of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 0.1 part of phenethyl oleate.

[0065] The preparation steps of the UV light curing adhesive are as follows:

[0066] Weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 0.5h, then add active diluent, photoinitiator and defoamer, control the reaction temperature to 75°C, continue stirring to react for 1h, and obtain UV light-curing adhesive after cooling.

[0067] Comparative Example 2

[0068] Compared with Example 1, the only difference is:

[0069] The preparation steps of the UV light curing adhesive are as follows:

[0070] Step 1, add 5g of silane coupling agent KH-560 to 100g of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), adjust the pH to 8, heat to 30°C, stir and hydrolyze for 1.5h, add 5g of nano zinc oxide, ultrasonically disperse until uniform, heat to 70°C, reflux for 3h, stop heating, separate, wash, and place in a 50°C vacuum drying oven for 12h to obtain modified zinc oxide;

[0071] Step 2: Weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70°C and stir to react for 0.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75°C, continue stirring to react for 1h, and obtain UV light-curing adhesive after cooling.

[0072] Comparative Example 3

[0073] Compared with Example 1, the only difference is:

[0074] A UV light curing adhesive, comprising the following raw materials in parts by weight:

[0075] 10 parts of o-phenylphenoxyethyl acrylate, 30 parts of isooctyl acrylate, 6 parts of modified zinc oxide, 20 parts of pentaerythritol triacrylate, 1 part of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 0.1 parts of phenethyl oleate.

[0076] Comparative Example 4

[0077] Compared with Example 1, the only difference is:

[0078] A UV light curing adhesive, comprising the following raw materials in parts by weight:

[0079] 20 parts of o-phenylphenoxyethyl acrylate, 65 parts of isooctyl acrylate, 6 parts of modified zinc oxide, 20 parts of pentaerythritol triacrylate, 1 part of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, and 0.1 parts of phenethyl oleate.

[0080] Application and performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 4:

[0081] The UV light-curing adhesive obtained in the embodiment and the comparative example was uniformly coated on the corona-treated BOPET film, and the film thickness was controlled to be 30-35 μm. The coated BOPET film was then placed in a UV curing machine for curing for 2 minutes and then taken out. After being covered with release paper, the sample was cut into the required standard size and the following tests were performed:

[0082] 1. Stickiness: Test the stickiness according to the standard GB / T 4851-2014.

[0083] 2. Aging resistance: The light transmittance was measured using a WGW photoelectric haze meter. After the film was exposed to a fluorescent ultraviolet lamp (UVA-340) for 48 hours, the light aging resistance of the sample was evaluated by visually observing the chromaticity of the sample compared with the sample. The full score is 5 points, and the degree of color change before and after illumination is used to score. Basically no change is 5 points.

[0084] 3. Antibacterial property: The antibacterial property of UV light curing adhesive is tested according to the standard GB 4789.2-2016.

[0085] The above test results are shown in Table 1:

[0086] Table 1

[0087]

[0088]

[0089] It can be seen from Table 1 that, compared with Comparative Examples 1-4, the UV light-curing adhesive obtained in Examples 1-5 has a high refractive index, and excellent light transmittance, aging resistance and antibacterial rate. It can be seen that the UV light-curing adhesive obtained by the preparation method of a UV light-curing adhesive provided in the present invention has a high refractive index, excellent mechanical strength and antibacterial properties.

[0090] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A UV light curing adhesive, characterized in that: By weight, it includes the following raw materials: 20-35 parts of hard monomer, 30-55 parts of soft monomer, 6-10 parts of modified zinc oxide, 20-35 parts of active diluent, 1-5 parts of photoinitiator, 0.1-1 parts of defoamer; The preparation steps of the modified zinc oxide are as follows: Add epoxidized zinc oxide and polyhexamethylene guanidine hydrochloride into deionized water, disperse them by ultrasonic for 15-20 minutes, stir them at room temperature for 46-48 hours, filter, wash and dry them to obtain modified zinc oxide.

2. A UV light curing adhesive according to claim 1, characterized in that: The dosage ratio of epoxidized zinc oxide, polyhexamethylene guanidine hydrochloride and deionized water is 0.2-0.3 g: 0.5-0.6 g: 100 mL.

3. The UV light curing adhesive according to claim 1, characterized in that: The preparation steps of epoxidized zinc oxide are as follows: Add silane coupling agent KH-560 to ethanol aqueous solution, adjust the pH to 8-8.5, heat to 30-35°C, stir and hydrolyze for 1.5-2h, add nano zinc oxide, ultrasonically disperse until uniform, heat to 70-75°C, reflux for 3-3.5h, stop heating, separate, wash, and vacuum dry to obtain epoxidized zinc oxide.

4. A UV light curing adhesive according to claim 3, characterized in that: The dosage ratio of silane coupling agent KH-560, ethanol aqueous solution and nano zinc oxide is 5-6g:100g:5-6.5g.

5. The UV light curing adhesive according to claim 1, characterized in that: The hard monomer is at least one of o-phenylphenoxyethyl acrylate, N,N-dimethylacrylamide, acryloylmorpholine, 2-phenoxyethyl acrylate and benzyl acrylate.

6. The UV light curing adhesive according to claim 1, characterized in that: The soft monomer is at least one of butyl acrylate, isooctyl acrylate, sec-butyl acrylate, stearic acid methacrylate and isodecyl methacrylate.

7. The UV light curing adhesive according to claim 1, characterized in that: The active diluent is at least one of ethoxylated bisphenol A dimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate and di(trimethylolpropane) tetraacrylate.

8. The UV light curing adhesive according to claim 1, characterized in that: The photoinitiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

9. The UV light curing adhesive according to claim 1, characterized in that: The defoaming agent is at least one of phenylethyl oleate, lauryl phenylacetate and polydimethylsiloxane.

10. A method for preparing a UV light-curing adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh each raw material by weight, mix the hard monomer and the soft monomer, heat to 70-90°C and stir to react for 0.5-1.5h, then add modified zinc oxide, active diluent, photoinitiator and defoamer, control the reaction temperature to 75-80°C, continue stirring to react for 1-1.5h, and obtain UV light-curing adhesive after cooling.